Acompanhamento longitudinal prospectivo de reabilitações mandibulares com overdentures sobre implantes submetidos a carga imediata - Zancopé, Karla (2011)
We conducted a prospective study in a group of patients treated at Faculty of Dentistry, in Federal University of Uberlandia rehabilitated with external regular hexagonal dental implants and mandibular overdentures with immediate loading in 2006, in order to assess the impact of the occlusal load in these implants. A total of 16 patients (4 men and 12 women, aged between 34 and 80 years, mean 62 years) were clinically and radiographically evaluated to determine parameters such as plaque index, gingivitis index, index of keratinized mucosa, bleeding index, probing depth, implant mobility and pain or discomfort of the implants. The anamnesis of the patients were also conducted, who responded to a questionnaire to measure their treatment satisfaction. The radiographic analysis was to determine the vertical and horizontal bone loss in implants, which had an average rate of 1.46 mm after a follow-up period of at least 48 months. It was concluded that regular hexagonal implant associated with mandibular overdenture, submitted to immediate loading, shows excellent survival rates, resulting in a safe, satisfying and less expensive treatment, when compared to conventional implant protocols.